Citizenship development of adolescents during the lower grades of secondary education - Geboers, Ellen; Geijsel, Femke; Admiraal, Wilfried; Jorgensen, Terrence; ten Dam, Geert (Journal of Adolescence, 2015)
The present study focuses on the development of citizenship competences of Dutch adolescents, including the political and social aspects as part of adolescents' daily lives. We followed 5070 adolescents aged 12–16 years across a three-year period in lower secondary education. The variance on school and student level was estimated and a three-level mixed-effects regression model was fit to analyze differences in citizenship development. The results indeed show development of citizenship competences during secondary school, but the observed patterns were not always positive. Students generally showed an increase in their citizenship knowledge, but a decline in their societal interest, prosocial ability and reflective thinking. Differences between groups of students could be explained by both schools and student characteristics. Especially girls and minority students developed the most citizenship competences. Understanding these differences is important for schools to improve their practices in ways that support the development of citizenship competences of various groups of students.
Keywords: Citizenship development; Citizenship education; Longitudinal analysis; Secondary education